STRUKTUR MODAL, INVESTMENT OPPORTUNITY SET, LIKUIDITAS DANNILAI PERUSAHAAN - Uzliawati, Lia; Nofianti, Nana; Ratnasari, Dwi Putri (University of Merdeka Malang, 2016)
AbstractThis research aims to know the influence of variable capital structure as measured by debt to equity ratio(DER), the investment opportunity set as measured by the market to book ratio (MBA) asset and liquidity asmeasured by the current ratio (LIQ) against the value of the company that projected through the Price to BookValue (PBV) on the banking company listed on the Indonesia stock exchange (idx) of the period 2009-2013.This research population is 39 banking company. Purposive Sampling was used as sampling techniques and29 companies selected as research samples. This study uses secondary data analysis and multiple regression.The results shows that the structure of capital and investment opportunity set has positive influence to thevalue of the companys liquidity and has no effect on the value of the company. While the size of the companyas a control variable has a significant positive influence to the value of the company. Simultaneous capitalstructure, investment opportunity set and the liquidity effect significantly to the value of the company.